Government Efforts to Boost Rice Farmers' Harvest Yields - Suwardi, Suwardi; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2024)
General Background: Economic development in developing countries aims to enhance economic growth, job opportunities, income distribution, and balance the economic structure. Specific Background: Indonesia, known as an agrarian country due to its fertile land, still relies on rice imports despite its agricultural potential. Knowledge Gap: The effectiveness of government roles in increasing rice production remains unclear, especially at the local level, where farmers face challenges with seed and fertilizer assistance. Aims: This study examines the government's role in increasing rice yields in Karangtanjung Village, Candi District, Sidoarjo Regency, focusing on its function as a stabilizer, innovator, pioneer, and implementer. Results: The findings reveal that the government’s role has been implemented but not fully effective. Farmers perceive challenges with assistance, notably in obtaining superior seeds and affordable, environmentally friendly fertilizers. Moreover, government efforts to enhance production through agricultural support face obstacles, including irrigation issues and limited farmer participation in training programs. Novelty: This study highlights the gaps in the current government interventions, emphasizing the need for improved policies to provide superior seeds and sustainable farming practices tailored to the specific conditions of Karangtanjung Village. Implications: For the government to enhance rice production effectively, there must be efforts to address the supply of superior seeds and environmentally friendly fertilizers, tailored training programs, and better irrigation systems to meet the needs of local farmers. This study underscores the importance of a more targeted approach in agricultural policy to ensure sustainable and increased crop yields. Highlights: Government acts as a stabilizer, innovator, pioneer, and implementer to support rice farming. Empowerment programs include providing seeds, fertilizer, irrigation systems, and agricultural machinery. Challenges remain in distribution, farmer education, and ensuring sustainable farming practices. Keywords: Government Role, Crop Yield, Rice Farmers, Agricultural Regulation, Village Empowerment